Game-changing alternatives to conventional fungicides: small RNAs and short peptides. Issue 3 (March 2022) - Rosa, Stefano; Pesaresi, Paolo; Mizzotti, Chiara; Bulone, Vincent; Mezzetti, Bruno; Baraldi, Elena; Masiero, Simona
Abstract : Fungicide use is one of the core elements of intensive agriculture because it is necessary to fight pathogens that would otherwise cause large production losses. Oomycete and fungal pathogens are kept under control using several active compounds, some of which are predicted to be banned in the near future owing to serious concerns about their impact on the environment, non-targeted organisms, and human health. To avoid detrimental repercussions for food security, it is essential to develop new biomolecules that control existing and emerging pathogens but are innocuous to human health and the environment. This review presents and discusses the use of novel low-risk biological compounds based on small RNAs and short peptides that are attractive alternatives to current contentious fungicides. Highlights: Pesticide use is currently a crucial component of intensive agriculture, guaranteeing protection from pathogens which otherwise would threaten the security of the food supply worldwide. The use of pesticides raises major concerns with respect to their impact on the environment and human health. In fact, soil and groundwater contamination represents a major societal issue, especially because of the persistence of highly toxic compounds. New biotechnological solutions need to be explored to discover safe and reliable alternatives to conventional pesticides. In recent years, double-stranded (ds)RNA and short peptide molecules have been shown to efficiently counteract oomycete and fungal infections. Short peptides and dsRNAs have high specificity, are readily degradable and effective in low doses and, in conjunction with novel delivery strategies, are suitable for precision agriculture systems.